2001
DOI: 10.1086/321540
|View full text |Cite
|
Sign up to set email alerts
|

Precipitating Condensation Clouds in Substellar Atmospheres

Abstract: We present a method to calculate vertical proÐles of particle size distributions in condensation clouds of giant planets and brown dwarfs. The method assumes a balance between turbulent di †usion and sedimentation in horizontally uniform cloud decks. Calculations for the Jovian ammonia cloud are compared with results from previous methods. An adjustable parameter describing the efficiency of sedimentation allows the new model to span the range of predictions made by previous models. Calculations for the Jovian… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
1,297
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 795 publications
(1,335 citation statements)
references
References 73 publications
(139 reference statements)
36
1,297
2
Order By: Relevance
“…This conclusion is also supported by observations of cloudy L-dwarfs, where models that assume the opacity of grains as given by the ISM distribution, without sedimentation, are a very poor match to the data (Chabrier et al, 2000) because they greatly overestimate the dust opacity. However, models that allow for grains to grow and sediment (see Ackerman & Marley, 2001) match spectroscopic data very well Burgasser et al, 2002;Marley et al, 2004). In short, the timescale argument against the core accretion-gas capture scenario is much weaker than had been previously thought, when opacities more appropriate to protoplanetary atmosphere conditions are used.…”
Section: Core Accretion-gas Capture Modelmentioning
confidence: 62%
“…This conclusion is also supported by observations of cloudy L-dwarfs, where models that assume the opacity of grains as given by the ISM distribution, without sedimentation, are a very poor match to the data (Chabrier et al, 2000) because they greatly overestimate the dust opacity. However, models that allow for grains to grow and sediment (see Ackerman & Marley, 2001) match spectroscopic data very well Burgasser et al, 2002;Marley et al, 2004). In short, the timescale argument against the core accretion-gas capture scenario is much weaker than had been previously thought, when opacities more appropriate to protoplanetary atmosphere conditions are used.…”
Section: Core Accretion-gas Capture Modelmentioning
confidence: 62%
“…Candidate species for condensation at the hot temperatures are silicates, iron (Lunine et al 1989;Ackerman and Marley 2001), or more exotic species present in brown dwarfs, such as TiO, VO, metal hydrides (Lodders 2003;Sharp and Burrows 2007). Other proposed hazes are soots (Zahnle et al 2010;Mousis et al 2011) or sulphur compounds (Zahnle et al 2009).…”
Section: Hot and Warm Jupiters And Neptunesmentioning
confidence: 99%
“…Most theory papers focused on irradiated hot Jupiters, emphasizing spectral features and 1D temperature/pressure profiles resulting from the intense heating by the host star (Seager & Sasselov 1998;Marley et al 1999;Sudarsky, Burrows, & Pinto 2000;Barman, Hauschildt & Allard 2001. Cloud modeling (Ackerman & Marley 2001;Cooper et al 2003) and atmospheric 200 S. Seager circulation (Showman & Guillot 2002;Cho et al 2003) were also expected to be important. Calculation of exoplanet illumination phase curves, polarization curves (Seager, Whitney, & Sasselov 2000), and especially transmission spectra Brown 2001;Hubbard et al 2001) set the stage for observed spectroscopy during transit.…”
Section: Exoplanet Atmospheres: a Theoretical Outlookmentioning
confidence: 99%